2016
DOI: 10.5897/ajb2016.15212
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of potential probiotic bacteria isolated from sorghum and pearl millet of the semi-arid tropics

Abstract: The present study was conducted to isolate and characterize probiotic properties of bacteria isolated from flour and batter samples of sorghum and pearl millet. A total of five different selective media including plate count agar, yeast glucose chloramphenicol agar, Bifidobacterium agar, actinomycetes isolation agar and de ManRogosa and Sharpe agar were used and the most prominent bacteria (which were found abundantly in the plate) were isolated and maintained on the respective media slants at 4°C for further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…Saarela et al (86) in their findings demonstrated that food produced from mono-species probiotics had an acidic and sour taste. The present study illustrated that all three isolates were compatible with each other to be used as multispecies, agreeing with the work of Rajyalakshmi et al (49). Regardless of the benefits linked with biofilm formation (87,88), biofilm tests for bacteria are vital to public health, since biofilmforming bacteria are noted to display reduced susceptibility to antimicrobial agents (89).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Saarela et al (86) in their findings demonstrated that food produced from mono-species probiotics had an acidic and sour taste. The present study illustrated that all three isolates were compatible with each other to be used as multispecies, agreeing with the work of Rajyalakshmi et al (49). Regardless of the benefits linked with biofilm formation (87,88), biofilm tests for bacteria are vital to public health, since biofilmforming bacteria are noted to display reduced susceptibility to antimicrobial agents (89).…”
Section: Discussionsupporting
confidence: 91%
“…Following the methodologies of Rajyalakshmi et al (49), the test of compatibility of the three isolates was conducted. Briefly, the three probiotic isolates were vertically streaked on an LB agar plate 5 mm apart, followed by a perpendicular streaking of 10 mm apart from each other.…”
Section: Compatibility Of the Three Isolatesmentioning
confidence: 99%
“…Hence, the compatibility test was carried out for the utilization of multispecies probiotics (Saarela et al, 2000;Rajyalakshmi et al, 2016;Kuebutornye et al, 2019). The compatibility test was performed as described previously by Rajyalakshmi et al (2016); Kuebutornye et al (2019). Briefly, the isolated bacteria were streaked vertically and perpendicularly on LB agar plates at a distance of 5 and 10 mm from each other.…”
Section: Compatibility Testmentioning
confidence: 99%
“…25 Many researchers have studied the pro and prebiotic aspects of millets and successfully suggested that using millets as a prebiotic is acceptable and beneficial. 26 The soluble fibre in millets reduced the risk of developing cardiovascular diseases by reducing triglycerides by 8% and 10% reduction in LDL and VLDL lipoproteins. In addition, consuming the millet decreased blood pressure, with the diastolic blood pressure by 5%.…”
Section: Discussionmentioning
confidence: 99%